1996
DOI: 10.1007/bf02087915
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fecal flora in a patient with short bowel syndrome

Abstract: D-Lactic acidosis associated with encephalopathy is a clinical condition that occurs in patients with short bowel syndrome. We studied the fecal flora and the composition of fecal water of a child who developed this unusual disorder. Bacteriological studies showed that the patient's stool contained a marked predominance of gram-positive anaerobes. Two strains were identified, Lactobacillus plantarum and Lactobacillus salivarius, as the main bacteria isolated. Fecal water showed pH 4.8 and total lactic acid (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 15 publications
1
19
0
4
Order By: Relevance
“…A more acidic environment (lower pH) encourages the growth of acid-resistant bacteria (including Lactobacilli ) and increases lactic acid production 27 . Several D-la case studies have shown an overgrowth of Lactobacillus species in stool samples 27-29 . With no comparative control group, we could not determine whether ME/CFS patients in our sample had an overgrowth of Lactobacilli .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A more acidic environment (lower pH) encourages the growth of acid-resistant bacteria (including Lactobacilli ) and increases lactic acid production 27 . Several D-la case studies have shown an overgrowth of Lactobacillus species in stool samples 27-29 . With no comparative control group, we could not determine whether ME/CFS patients in our sample had an overgrowth of Lactobacilli .…”
Section: Introductionmentioning
confidence: 89%
“…The pH level influences bacterial composition. A more acidic environment (lower pH) encourages the growth of acid-resistant bacteria (including Lactobacilli ) and increases lactic acid production 27 . Several D-la case studies have shown an overgrowth of Lactobacillus species in stool samples 27-29 .…”
Section: Introductionmentioning
confidence: 99%
“…The dysbiosis is distinguished by an increased colonisation of lactic acid-producing bacteria, particularly bacteria that produce d -lactate (e.g., Lactobacillus fermenti, L acidophilus, and Streptococcus ; see review by Petersen [13]). An overgrowth of Lactobacilli has been identified in SBS patients with increased d -lactate levels [26, 28, 37, 47, 64, 68, 72, 74, 75, 103]. This dysbiosis has been proposed as a result of an impaired small intestine, either due to congenital causes, surgery for midgut volvulus, gangrene or inflammatory bowel disease [104]; functional SBS and carbohydrate malabsorption [32, 36]; or colonic stagnation [62].…”
Section: Part B Narrative Reviewmentioning
confidence: 99%
“…Increased bacterial fermentation can further reduce bowel motility [31], alter colonic pH and change the level of bacterial metabolites. This can include a reduction in volatile fatty acids [26] and increased d -lactate production [shown in 26, 54, 64, 66, 75, 105]. …”
Section: Part B Narrative Reviewmentioning
confidence: 99%
See 1 more Smart Citation